IMPLEMENTASI TEKNOLOGI BERBASIS ENERGI TERBARUKAN PADA PRODUKSI ABON IKAN NILA DI YAYASAN DARUL HIKMAH AL HASANI, MALANG - Sunaryono; Nandang Mufti; Aripriharta; Nurul Putri Wulandari; Arisma Nurul Fauziyah; Achmad Khofiyulloh; Sunaryono Sunaryono; Aripriharta Aripriharta (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The solar-powered Nila floss production system was developed to address the issues encountered by the Darul Hikmah Al Hasani Foundation in Merjosari, Malang. Although the partner owns nila fish ponds with high potential, they have not been optimally utilized as an income source. This technology enhances production effectiveness and efficiency while reducing operational costs by utilizing solar energy. The system integrates several machines: a bone–meat separator, an autoclave, a meat shredder, a mixt-roaster, and an oil spinner, all powered by solar panels. This application of scientific knowledge provides tangible benefits for the partner, including cost savings, more efficient production, and enhanced income generation through the development of value-added fish products. The program will run for ten months, starting with preparation and installation, followed by operational training and mentoring. A marketing analysis will also be conducted to strengthen product competitiveness and expand market reach for Nila Fish Floss.